Historiográfia a szintézisíráshoz 1: Az összeomlás kora: 1918. október 31.–1920. március 1. - Gulyás, László (Közép-Európai Közlemények, 2023)
The important task of national-conservative-bourgeios historiography nowadays is to create of synthesis of the history of the „short Hungarian 20th century. The presen study is one of the first steps in this work. It reviews Hungarian language literature dealing with the age of the collapse (31 October 1918–1920 March 1919).